Social representations of help: Perceptions of vulnerable populations being helped - Bignone, Lisa (2020)
The aim of this study, conducted through the Social Representation Theory (Moscovici, 1976) lenses, was to investigate the perceptions of help recipients, so, to understand the shared representations on Help itself and on the Helping Institutions, the self-perceptions as aid recipients and the perceptions about the potential Social Status Distance with regard to the their helpers. Participants were twenty-five people between 18 and 70-years-old members of vulnerable groups that benefited from help programs offered by Non-Profit Institutions/Organizations. The study was conducted through semi-structured interviews, a methodology commonly used in Social Representation Theory (Moscovici, 1976) and in the structural approach to it (Abric, 1984; Vergès, 1994). Eight-hundred free evocations and 149 words were produced, all the data were analyzed with open-EVOC software (2000), a software designed for Social Representations data analysis. Results showed, differently from the literature on autonomy and dependency orientations to help (Nadler, 1997; 1998; 2002; 2015), the importance, at different levels, of both orientations. This study showed the importance, for the recipients of help, of being protagonists, active and autonomous in the process of improving their psychological and material resources, but also the importance of enjoying material goods, even if it means depending on the institution. Results were discussed as a potential contribute to the design of help programs that might provide greater benefits and well-being to help recipients.